Light-Driven Preparation, Microstructure, and Visible-Light Photocatalytic Property of Porous Carbon-Doped TiO2 - Xiao-Xin Zou; Guo-Dong Li; Jun Zhao; Juan Su; Xiao Wei; Kai-Xue Wang; Yu-Ning Wang; Jie-Sheng Chen (International Journal of Photoenergy)
Highly porous carbon-doped TiO2 (C-TiO2) has been prepared, for the first time, through a light-driven approach using crystalline titanium glycolate (TG) as the single-source precursor. Although the nonthermally prepared porous C-TiO2 is amorphous, it shows a remarkable visible-light photocatalytic activity higher than that of nitrogen-doped TiO2 (N-TiO2) due to its significant surface area (530 m2/g) and pore-rich structure. X-ray photoelectron, electron paramagnetic resonance, and UV-Vis diffuse reflectance spectroscopy reveal that the as-prepared porous C-TiO2 photocatalyst contains Ti–O–C bonds which result in visible-light absorption of the material at wavelengths less than 550 nm. Furthermore, it is discovered that the Ti–O–C bonds in the as-prepared C-TiO2 is easily transformed to coke-type species under mild thermal treatment (200°C). The resulting coke-containing porous TiO2 is an even better visible-light photocatalyst, almost twice as effective as N-TiO2, because of its stronger visible-light absorption. The Ti–O–C and the coke-containing porous TiO2 materials follow two different mechanisms in the visible-light photocatalysis process for degradation of methylene blue.